Plant extracts with antisickling propensities: a feasible succour towards sickle cell disease management- a mini review - Sahu, Meena; Singh, Varsha; Yadav, Somnath; Harris, K K (Journal of Phytology, 2012)
Sickle cell disease (SCD) is known to be one of the diseases wrecking most parts of the globe without any discrimination of ethnic or racial standards. It is characterized by a variety of symptoms including, shortness of breath, heart palpitations, abdominal pains, aches and pains in the muscle. The crisis stage is characterized by severe pain in the head and whole body. In the stage of crises if the percentage of sickled erythrocytes can be some how lowered we can expect a great relief to the patient. This could also serve a major step to-words management of the SCD. Phytochemicals in the plant extracts have the therapeutic activity and is used in traditional practice by the traditional healers. Many plant extracts have been used to bring about reversal of the sickled erythrocytes in vitro. The present communication reviews the available literature reporting anti-sickling properties of a number of plants extracts on human blood samples.